Transport of Pseudomonas aeruginosa in Polymer Solutions - Savorana, Giovanni; Geisel, Steffen; Cen, Tianyu; Ling, Yuya; Stocker, Roman; Rusconi, Roberto; Secchi, Eleonora (Frontiers in Physics, 2022)
Bacteria often live surrounded by polymer solutions, such as in animal respiratory, gastrointestinal, and reproductive tracts. In these systems, polymer solutions are often exposed to fluid flow, and their complex rheology can affect the transport of chemical compounds and microorganisms. Recent studies have focused on the effect of polymer solutions on the motility of bacteria in the absence of fluid flow. However, flow can be a game-changer on bacterial transport, as demonstrated by the depletion of motile bacteria from the low-shear regions and trapping in the high-shear regions in simple fluids, even for flows as simple as the Poiseuille one. Despite the relevance of polymer solutions in many bacterial habitats, the effect of their complex rheology on shear-induced trapping and bacterial transport in flow has remained unexplored. Using microfluidic experiments and numerical modeling, we studied how the shear rate and the rheological behavior of Newtonian and non-Newtonian polymer solutions affect the transport of motile, wild-type Pseudomonas aeruginosa in a Poiseuille flow. Our results show that, in Newtonian solutions, an increase in viscosity reduces bacterial depletion in the low-shear regions at the microchannel center, due to a reduction in the bacterial swimming velocity. Conversely, in the non-Newtonian solution, we observed a depletion comparable to the buffer case, despite its zero-shear viscosity being two orders of magnitude higher. In both cases, bacterial swimming and polymer fluid rheology control the magnitude of bacterial depletion and its shear-rate dependence. Our observations underscore the importance of the rheological behavior of the carrier fluid in controlling bacterial transport, in particular, close to surfaces giving rise to velocity gradients, with potential consequences on surface colonization and biofilm formation in many naturally relevant microbial habitats.